2018
DOI: 10.4269/ajtmh.18-0169
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Assessment of a Hotspot with Persistent Bancroftian Filariasis in Coastal Sri Lanka

Abstract: Abstract.The Sri Lankan Anti-Filariasis campaign distributed five rounds of mass drug administration (MDA with diethylcarbamazine plus albendazole) to some 10 million people in eight districts between 2002 and 2006. Sri Lanka was recognized by the WHO for having eliminated lymphatic filariasis (LF) as a public health problem in 2016. However, recent studies by our group documented pockets with persistent LF in coastal Sri Lanka, especially in Galle district. The present study was performed to reexamine an area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 20 publications
2
55
0
Order By: Relevance
“…Our study showed that population representative surveys of older children have the potential to reduce NNTest, and cost-effectiveness could be maintained by conducting the surveys at schools in areas where school attendance rates are high, e.g. testing age [8][9][10][11][12] year-olds in elementary schools, or age [13][14][15][16][17] year-olds at secondary school. Furthermore, testing [8][9][10][11][12] year-olds in TAS-2, TAS-3, and beyond is consistent with the rationale behind TAS, i.e targeting age groups who have lived their entire lives during and/or after MDA, so any positive cases would indicate incident infection and therefore ongoing transmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study showed that population representative surveys of older children have the potential to reduce NNTest, and cost-effectiveness could be maintained by conducting the surveys at schools in areas where school attendance rates are high, e.g. testing age [8][9][10][11][12] year-olds in elementary schools, or age [13][14][15][16][17] year-olds at secondary school. Furthermore, testing [8][9][10][11][12] year-olds in TAS-2, TAS-3, and beyond is consistent with the rationale behind TAS, i.e targeting age groups who have lived their entire lives during and/or after MDA, so any positive cases would indicate incident infection and therefore ongoing transmission.…”
Section: Discussionmentioning
confidence: 99%
“…testing age [8][9][10][11][12] year-olds in elementary schools, or age [13][14][15][16][17] year-olds at secondary school. Furthermore, testing [8][9][10][11][12] year-olds in TAS-2, TAS-3, and beyond is consistent with the rationale behind TAS, i.e targeting age groups who have lived their entire lives during and/or after MDA, so any positive cases would indicate incident infection and therefore ongoing transmission. School-based TAS of older children should therefore be considered, and together with adjunct surveillance strategies discussed above, could potentially optimise the detection of residual infections while maintaining cost-effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Transmission zones in W. bancrofti are highly dependent on variation in vector density, survival, and competence for transmission and whether vector mosquitoes are diurnal, nocturnal, or sub-nocturnal. In areas with postintervention recrudescence, there are sometimes infection "hot spots": a localized area where prevalence is significantly higher than surrounding areas (e.g., American Samoa: Lau et al, 2014;Lau et al, 2016;Lau et al, 2017;Sri Lanka: Rao et al, 2014;Rao et al, 2017;Rao et al, 2018). Potential explanations for recrudescence include expansion of infections from hot spots when mosquitoes take up and transmit parasites to geographically nearby communities or when infectious people visit other communities, slow but insidious increase in frequency and intensity of transmission from widespread infections at low prevalence that were not detected or were considered (incorrectly) to be under the threshold for stopping MDA, or migrants from other endemic regions continue to introduce new parasites, if the evaluation unit is inappropriately small.…”
Section: Lymphatic Filariasismentioning
confidence: 99%
“…WHO, while recommending MX for post-MDA surveillance, suggested focussing on mosquito surveys on individual villages to provide an indication of the presence of residual infection (residual hotspots) [46] at village level [18]. Rao et al [48], after analysing MX data by sites reported persistent infection in many sites in an EU in Sri Lanka that stopped MDA post-5 rounds after demonstrating transmission interruption through TAS. Our MX survey detected 5 clusters with residual infection compared to 3 clusters detected by community-based Mf-survey or 2 schools by Ag-survey through TAS, suggesting that MX was more sensitive than community-based Mf-survey or school-based Ag-survey by TAS for detecting residual infection in areas under post-MDA surveillance.…”
Section: For Assessing Residual Hotspotsmentioning
confidence: 99%